THE INFLUENCE OF PRODUCTION FACTORS ON THE CLINICAL FEATURES OF PSORIASIS IN THE PATHWAY FITTER - Карпова, Ольга Анатольевна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2021)
This article describes the clinical observation of the features of the severity and course of psoriasis vulgaris patient, working as a lineman way, under the influence of chemical, meteorological, physical environment factors relating to class 2, as well as heavy labor subclass harm 3.1. The presented clinical case shows how the combined effect of chemical, meteorological, physical, and factors of severity and intensity of the work process contributes to early debut, more severe and progressive course of extensive psoriasis in a patient without comorbidities.